Vocational Public Relations Education: Does It Meet Employers’ Entry-level Needs? - Maulidiyanti, M; Suciati, P (KnE Social Sciences, 2018)
In this new age of globalization, higher education plays an increasingly important role in preparing a workforce that meets the rapidly changing industry needs. The article examines the entry-level skills and competency gap that exist between Public Relations (PR) and employer needs (agency, corporate and government) in entry-level positions and curriculum in Vocational Public Relations (PR) in Universitas Indonesia. This idea comes up from the phenomenon that there are so many PR positions handled by people from other fields, not from PR (engineering, politics, etc.) We used a content analysis of entry-level public relations job postings and also deep interview. Content analysis data are measured to explore the areas that have a greatest and least demand in entry-level public relations positions in relation to education. This research analyzes PR job posting by PR Agency, Multinational Private Company and Government Institution. The result shows us the gap between curriculum and entry-level requirement through its gap analysis. To strengthen the data, we also use qualitative gap analysis from in-depth interview with users from three different sectors. This study found that there are four gap items in vocational PR curriculum, such as: Media Monitoring Skills, Digital Communications Skill (plan, execute and evaluate), PR Documents writings and Photography & Videography basic skill. Author’s suggestion is also provided for strengthening the current vocational public relations curriculum and improving the communication of key strengths in job posting. Keywords: public relations, education, curriculum, requirement